Recent progress in understanding the role of ecdysteroids in adult insects: Germline development and circadian clock in the fruit fly Drosophila melanogaster. Issue 1 (December 2015) - Uryu, Outa; Ameku, Tomotsune; Niwa, Ryusuke
Abstract Steroid hormones are one of the major bioactive molecules responsible for the coordinated regulation of biological processes in multicellular organisms. In insects, the principal steroid hormones are ecdysteroids, including 20-hydroxyecdysone. A great deal of research has investigated the roles played by ecdysteroids during insect development, especially the regulatory role in inducing molting and metamorphosis. However, little attention has been paid to the roles of these hormones in post-developmental processes, despite their undisputed presence in the adult insect body. Recently, molecular genetics of the fruit flyDrosophila melanogaster has revealed that ecdysteroid biosynthesis and signaling are indeed active in adult insects, and involved in diverse processes, including oogenesis, stress resistance, longevity, and neuronal activity. In this review, we focus on very recent progress in the understanding of two adult biological events that require ecdysteroid biosynthesis and/or signaling inDrosophila at the molecular level: germline development and the circadian clock.